Alternative for Germany: Reconfiguring German Democracy. - Reber, April L. (German Politics & Society)
Germany is a liberal democracy that upholds individual rights and the rule of law. Nevertheless, as part of its militant democracy, it has partially legalized and certainly socialized illiberal efforts. The political party Alternative for Germany (AfD) emerged from the schism created by two (il)liberalisms in German democratization. Founded in 2013 on Euroskeptic principles, the AfD has experienced multiple power struggles and has evolved into an anti-Islam, anti-migration party that promotes positive memory politics and German national interests. I consider the AfD as a recent iteration of the ongoing project to redefine German democracy by keeping it aligned with enduring political and ethnocultural legacies. In this article, I discuss two approaches taken to this effect: the logics of "normal" and speech rights.